2018
DOI: 10.4309/jgi.2018.39.4
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Behaviours and Problem Gambling Among Older Adults Who Patronize Ontario Casinos or Racinos

Abstract: This study examined the rate of gambling problems among Ontario older adults at gambling venues. Herein we describe an intercept survey that took place at casinos and horse racing tracks with slot machines or other forms of casino games (racinos) in southwestern Ontario, Canada. This method provided a significant opportunity to obtain a large sample of older adult casino gamblers in order to understand the gambling habits and gambling problems of this population. We used an intercept recruitment method to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Urban casino gambling is even more accessible, available, and acceptable in the northeast; yet, the risks of increased urban casino-gambling participation, which could potentially impact the prevalence of gambling-related problems such as economic distress, mental disorders, and health problems (Ariyabuddhiphongs, 2012;Conway, 2015;Martin et al, 2011;Stansbury et al, 2015;Tolchard, 2015;Tong and Chim, 2013;Turner et al, 2018) for casino patrons and the community-atlarge have not been exhausted in the literature. Hardly any research on urban casinos and how they impact host environments in major metropolitan cities were uncovered.…”
Section: Results From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Urban casino gambling is even more accessible, available, and acceptable in the northeast; yet, the risks of increased urban casino-gambling participation, which could potentially impact the prevalence of gambling-related problems such as economic distress, mental disorders, and health problems (Ariyabuddhiphongs, 2012;Conway, 2015;Martin et al, 2011;Stansbury et al, 2015;Tolchard, 2015;Tong and Chim, 2013;Turner et al, 2018) for casino patrons and the community-atlarge have not been exhausted in the literature. Hardly any research on urban casinos and how they impact host environments in major metropolitan cities were uncovered.…”
Section: Results From the Literaturementioning
confidence: 99%
“…Gambling disorder and problem gambling are frequently used interchangeably in the gambling literature; however, studies that examined casinos, casino participation, and socio-economic aspects of casino gambling, commonly used problem gambling (Ashley and Boehlke, 2012;Barnes et al, 2013;Baxter et al, 2016;Conway, 2015;Gattis and Cunningham-Williams, 2011;Hodgins and Petry, 2016;Stansbury et al, 2015;Tong and Chim, 2013;Turner et al, 2018;Welte et al, 2016a;Welte et al, 2016b).…”
Section: Results From the Literaturementioning
confidence: 99%
“…In addition, we found that the involvement of gamers was not predictive of how likely they are to watch ads for currency. It could be thatas Turner et al (2018) reported-the risk factors of gambling such as being unmarried, having a lower income, and, ironically, being employed-correspond to those who are most invested in ad watching. Whales may not, after all, be those with the most money, but those who perceive themselves as spending the most money and thus are most interested in supplementing it by whatever means necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies an association between the nature of wanting to acquire more in-game currency and ad watching. Notably, in this genre of gaming, with such a strong association with gambling (Brooks & Clark, 2019;Turner et al, 2018), it is interesting to see the potential implications of advertisers targeting a vulnerable public, players with gaming disorders who are enjoying a game type that may constitute gambling. Because gambling addictions typically suggest a lack of volitional control, in order to earn the currency in the games that they are addicted to, gamers may be willing to engage in behaviour that may normally be considered annoying (e.g., ad watching).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bus tours, two recent studies have shed light on this issue. Van der Mass et al (2017;, in two separate studies, found that problem gambling scores are higher among those who report using a bus to get to the casino (see also Turner, et al, 2018). These studies highlight the need to collect empirical evidence from older adults in order to make evidence-based decisions.…”
Section: 3mentioning
confidence: 99%